2009
DOI: 10.1086/648477
|View full text |Cite
|
Sign up to set email alerts
|

Infection withMycobacterium tuberculosisBeijing Genotype Strains Is Associated with Polymorphisms inSLC11A1/NRAMP1in Indonesian Patients with Tuberculosis

Abstract: Differences in host immune genes may predispose to tuberculosis caused by particular Mycobacterium tuberculosis genotypes. We examined this hypothesis in Indonesia by spoligotyping M. tuberculosis isolates recovered from 336 patients with pulmonary tuberculosis and typing the patients' SLC11A1 gene (formerly known as "NRAMP1"), which is involved in susceptibility to tuberculosis. The M. tuberculosis Beijing genotype, which comprised 29.8% of all isolates, was strongly associated with 2 polymorphisms in SLC11A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 15 publications
3
63
1
Order By: Relevance
“…PGL which has been identified in other Euro-American strains, has been linked to hypervirulence phenotypes in laboratory studies that used macrophages and animal models (Coscolla and Gagneux, 2010;Malik and Godfrey-Faussett, 2005). Furthermore, East Asian isolates have been associated with more severe cavitary disease (Cowley et al, 2008;Parwati et al, 2010;van Crevel et al, 2009). Combined, our data provide evidence to demonstrate that 'modern' lineages particularly East Asian and Euro-America strains evolved non-lethal but aggressive/destructive properties in the lungs which enhanced intergenerational propagation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…PGL which has been identified in other Euro-American strains, has been linked to hypervirulence phenotypes in laboratory studies that used macrophages and animal models (Coscolla and Gagneux, 2010;Malik and Godfrey-Faussett, 2005). Furthermore, East Asian isolates have been associated with more severe cavitary disease (Cowley et al, 2008;Parwati et al, 2010;van Crevel et al, 2009). Combined, our data provide evidence to demonstrate that 'modern' lineages particularly East Asian and Euro-America strains evolved non-lethal but aggressive/destructive properties in the lungs which enhanced intergenerational propagation.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have described host, pathogen, environmental, and lifestyle factors associated with outcomes after TB exposure, after latent Mycobacterium tuberculosis infection, or after TB disease (Blaser and Kirschner, 2007;Caws et al, 2008;Coscolla and Gagneux, 2010;Kato-Maeda et al, 2001;Malik and Godfrey-Faussett, 2005;Pasipanodya et al, 2012b;van Crevel et al, 2009). Clinical studies have not demonstrated clear relationships between host genetic susceptibility factors, M. tuberculosis lineages, and TB outcomes (Caws et al, 2008;van Crevel et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A study of Vietnamese subjects detected an association between the C allele of TLR2 597T/C and TB caused by East Asian/Beijing genotype M. tuberculosis strains (41). Genetic variations in the 3=-UTR and the D543N SNP of SLC11A1 (NRAMP1) were significantly associated with susceptibility to infection by M. tuberculosis Beijing strains in Indonesian TB patients (241) and with the incidence of MDR-TB cases in Japan (223), which suggests an influence of bacterial genotype/ phenotype on host innate immunity. To what extent these same variants also interact with other M. tuberculosis strains remains to be tested.…”
Section: Factors That Influence the Functions Of Innate Immune Gene Pmentioning
confidence: 99%
“…A single gene that is not associated with susceptibility to TB will show an association if combined with other genes [38,39]. Besides, gene-agent interaction showed association of a certain host gene with a certain strain of Mycobacterium tuberculosis [40,41].…”
Section: Discussionmentioning
confidence: 99%